2014
DOI: 10.1007/s00261-014-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of CT findings for bowel ischemia and necrosis in closed-loop small-bowel obstruction

Abstract: Reduced enhancements of bowel wall and mesenteric veins were good indicators of bowel ischemia or necrosis. On the contrary, engorgement of the mesenteric veins was a predictor of a viable bowel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
(79 reference statements)
2
43
0
Order By: Relevance
“…Decreased or absent mural enhancement after administration of IV contrast is a useful, highly specific, indicator of intestinal ischemia (95-100%), despite variable sensitivity of 40-60% [46,57,58]. A recent meta-analysis showed that decreased mural enhancement was more predictive of ischemia than any other single CT sign [59,60]. This sign was 100% specific and 56% sensitive for bowel ischemia [57][58][59][60].…”
Section: Abdominal Ctmentioning
confidence: 91%
See 2 more Smart Citations
“…Decreased or absent mural enhancement after administration of IV contrast is a useful, highly specific, indicator of intestinal ischemia (95-100%), despite variable sensitivity of 40-60% [46,57,58]. A recent meta-analysis showed that decreased mural enhancement was more predictive of ischemia than any other single CT sign [59,60]. This sign was 100% specific and 56% sensitive for bowel ischemia [57][58][59][60].…”
Section: Abdominal Ctmentioning
confidence: 91%
“…A recent meta-analysis showed that decreased mural enhancement was more predictive of ischemia than any other single CT sign [59,60]. This sign was 100% specific and 56% sensitive for bowel ischemia [57][58][59][60]. Other CT signs of ischemia include bowel wall thickening and mucosal thumbprinting from intramural edema, inflammation, or hemorrhage; pneumatosis intestinalis from intramural gas produced by bacteria; and streaky mesentery from adjacent inflammatory infiltration as listed in Table 2 [11•, 24].…”
Section: Abdominal Ctmentioning
confidence: 97%
See 1 more Smart Citation
“…Balthazar et al reported that the detection of ischemic change in the bowel wall, attached mesentery, or both of on CT was diagnostic of bowel ischemia [19]. Nakashima et al reported that reduced enhancements of the bowel wall and mesenteric vessels was reliable for detecting bowel ischemia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Active small bowel bleeding at multiphase CTE is observed as a gradual accumulation of contrast material within the bowel lumen [8].…”
Section: Emergencymentioning
confidence: 99%